Swimming to Catalina : a novel - Woods, Stuart (New York : Harper Paperbacks, 1998)
When an actor's wife is abducted in Hollywood, the husband turns for help to lawyer Stone Barrington, the wife's ex-boyfriend. For Barrington, it is a dangerous assignment as the Mafia is involved, but he knows danger, having been a New York policeman.
Koleksi Sumbangan : Dr. Syed Husin Ali.
Keywords: Barrington, Stone (Fictitious character) -- Fiction; Private investigators -- California -- Fiction; Missing persons -- Fiction